2022
DOI: 10.3389/fphar.2022.964793
|View full text |Cite
|
Sign up to set email alerts
|

New insights into natural products that target the gut microbiota: Effects on the prevention and treatment of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignant carcinomas. CRC is characterized by asymptomatic onset, and most patients are already in the middle and advanced stages of disease when they are diagnosed. Inflammatory bowel disease (IBD) and the inflammatory-cancer transformation of advanced colorectal adenoma are the main causes of CRC. There is an urgent need for effective prevention and intervention strategies for CRC. In recent years, rapid research progress has increased our understanding of gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 176 publications
1
11
0
Order By: Relevance
“…Late re-hemorrhage and a lower rate of thorough obliteration are two main challenges for usage of the endovascular coiling. These disadvantageous of endovascular coiling have been explained and resolved by new achievements 2 , 3 . The usage of stent is recognized as an important method for the reduction of the aneurysm rupture risk in patients with high sac section area.…”
Section: Introductionmentioning
confidence: 99%
“…Late re-hemorrhage and a lower rate of thorough obliteration are two main challenges for usage of the endovascular coiling. These disadvantageous of endovascular coiling have been explained and resolved by new achievements 2 , 3 . The usage of stent is recognized as an important method for the reduction of the aneurysm rupture risk in patients with high sac section area.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the literature survey revealed that the synthesized compounds have remarkable cytotoxicity levels comparable with previously reported compounds. 78,79…”
Section: In Vitro Cytotoxicity Activitymentioning
confidence: 99%
“…Since the expression of circRNAs is dysregulated in several cancer types, they are known as a potential diagnostic biomarkers in cancer (Wu et al, 2020). For example, He et al have shown that hsa circ 0000069 is highly expressed in colorectal cancer, one of the most common malignant carcinomas, and associated with the degree of clinical features (Guo et al, 2016; Lu et al, 2022).…”
Section: Ncrnas Applications In Cancer Treatmentmentioning
confidence: 99%